2018
DOI: 10.4103/ijdvl.ijdvl_1021_16
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, treatment and prevention of herpes zoster: A comprehensive review

Abstract: Herpes zoster is a major health burden that can affect individuals of any age. It is seen more commonly among individuals aged ≥50 years, those with immunocompromised status, and those on immunosuppressant drugs. It is caused by a reactivation of varicella zoster virus infection. Cell-mediated immunity plays a role in this reactivation. Fever, pain, and itch are common symptoms before the onset of rash. Post-herpetic neuralgia is the most common complication associated with herpes zoster. Risk factors and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1
29

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 141 publications
2
54
1
29
Order By: Relevance
“…[ 15 ] Studies have shown that the global incidence of HZ increases year by year. [ 16 , 17 ] Postherpetic neuralgia (PHN) is the most serious complications in HZ, is characterized by severe pain, its incidence of 5% to 30%, when patients older than 85 years old was 50%, and the higher incidence of pain and sustainable for several months to several years, the serious influence the patient's quality of life, brings the serious economic burden to society, caused a public health problem. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Studies have shown that the global incidence of HZ increases year by year. [ 16 , 17 ] Postherpetic neuralgia (PHN) is the most serious complications in HZ, is characterized by severe pain, its incidence of 5% to 30%, when patients older than 85 years old was 50%, and the higher incidence of pain and sustainable for several months to several years, the serious influence the patient's quality of life, brings the serious economic burden to society, caused a public health problem. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…When the VZV-specific immunity decreases, the latent virus in the ganglions reactivates, replicates, and then various HZ or ZSH symptoms appear [ 4 ]. Many factors affecting cellular immunity may cause the reactivation of the VZV [ 17 ]. These risk factors for VZV reactivation include: old age, cellular immunodeficiency, genetic susceptibility, trauma, systemic diseases (such as diabetes, kidney disease, fever, hypertension, etc.…”
Section: Pathogenesis Of Zshmentioning
confidence: 99%
“…Аналіз поліморфізму гена ІЛ-10 (rs 1800872) залежно від клінічної форми та ступеня тяжкості оперізувального герпесу показав, що ТТ генотип вірогідно частіше реєстрували у хворих із тяжким перебігом захворювання (86,7 % проти 48,6 %, р = 0,01), проте не впливав на формування певних клінічних форм захворювання (р > 0,05). У хворих на оперізувальний герпес поліморфізм гена ІЛ-10 (rs 1800872) впливав на тяжкість перебігу захворювання: генотип TT асоціювався з тяжким перебігом захворювання (р = 0,01) і розвитком ускладнень неврологічного характеру (р = 0,03), що були представлені менінгітом (6), синдромом Рамсея-Ханта (3) та наступним формуванням постгерпетичної невралгії (3), а також офтальмологічного характеру (р = 0,0001), які були представлені герпетичним блефарокон'юнктивітом (16), кератоувеїтом (3), іридоциклітом (1), субкон'юнктивальним крововиливом (1). На відміну від генотипу TT, генотип TG гена ІЛ-10 (rs 1800872) мав асоціацію з розвитком ускладнень, що пов'язані з приєднанням вторинної бактеріальної мікрофлори (χ 2 = 4,5, р = 0,03), частота розвитку яких не залежала від тяжкості перебігу оперізувального герпесу (р > 0,05).…”
unclassified
“…Анализ полиморфизма гена ИЛ-10 (rs 1800872) в зависимости от клинической формы и степени тяжести опоясывающего герпеса показал, что генотип ТТ достоверно чаще регистрировали у больных с тяжелым течением заболевания (86,7 % против 48,6 %, р = 0,01), однако не влиял на формирование определенных клинических форм заболевания (р > 0,05). У больных опоясывающим герпесом полиморфизм гена ИЛ-10 (rs 1800872) влиял на тяжесть течения заболевания, а именно генотип TT ассоциировался с тяжелым течением заболевания (р = 0,01) и развитием осложнений неврологического характера (р = 0,03), которые были представлены менингитом (6), синдромом Рамсея-Ханта (3) и последующим формированием постгерпетической невралгии (3), а также офтальмологического характера (р = 0,0001), которые были представлены герпетическим блефароконъюнктивитом (16), кератоувеитом (3), иридоциклитом (1), субконъюнктивальным кровоизлиянием (1). В отличие от генотипа TT, генотип TG гена ИЛ-10 (rs 1800872) имел ассоциацию с развитием осложнений, связанных с присоединением вторичной бактериальной микрофлоры (χ 2 = 4,5, р = 0,03), частота развития которых не зависела от тяжести течения опоясывающего герпеса (р > 0,05).…”
unclassified
See 1 more Smart Citation